Moisture Content and Absorption Levels of Carbon Dioxide in Binuang Bini (Octomeles sumatrana Miq) Trees For Climate Change Management - Jacob Kailola; Gun Mardiatmoko; Radios Simanjuntak; Agustinus Kastanya (Jurnal Manajemen Hutan Tropika, 2021)
Binuang bini (Octomeles sumatrana Miq) is a fast-growing tree with numerous economic benefits, such as the provision of wood for carpentry purposes, building boards, water management, and absorption of carbon dioxide (CO2). Therefore, this tree species has great potential and needs to be included in Reducing Emission from Deforestation and Forest Degradation (REDD)+'s mitigation program to tackle climate change. In its development, REDD+ has made it possible to carry out carbon trading in the world. Therefore, countries capable of performing protective functions and carry out reforestation, afforestation, and restoration, have the opportunity to be involved in world carbon trading. This study aims to determine the moisture content and carbon absorption rate of Binuang bini trees as a first step to regulate the allometric equation using destructive and laboratory analysis. The results show that the water content in the roots, leaves, as well as the base, middle, and tip of the stem were: 73.69%, 68.39%, 65.59%, 61.22%, and 66.26%, respectively. Furthermore, the sample test results indicate a very close relationship between carbon concentration and absorbance in the O. sumatrana tree with a simple linear regression equation: Y = 0.002X + 0.0593 with R2 = 0.9896. Therefore, this regression equation can be used to calculate the carbon concentration sample for the O. sumatrana tree fraction. The carbon content in 3 tree samples with a breast height diameter of 9.24 cm, 10.08 cm, and 11.68 cm was 2,585 kg. 2,913 kg, and 4,654 kg, respectively. In addition, the carbon sequestration for each tree diameter per year is 1.581 kg year-1, 1,782 kg year-1and 2,847 kg year-1, respectively.